A breathing microbattery: Zn/MCM-41/O2 system - Saputra, Hens; Assayidatul Laila, Nor Hairin; Sutjipto, Agus Geter Edy; Muhida, Riza; Mohd Hanafi, Ani; Othman, Raihan (2010)
A high energy density, Zn/MCM-41/O2 microbattery of 1.5 V, measured 1 cm2 area and 100 μm thick, was able to produce current as high as 27 mA. The electrochemical system is popularly dubbed as breathing battery since it utilizes oxygen from ambient air, which is free, unlimited, and does not requires storage. A novel nanoporous inorganic MCM-41 material which consists of hexagonally-ordered pore structure has been introduced as an ionic exchange membrane-cum-electrolyte matrix. MCM-41 material is characterized by its large surface area and pore volume, narrow pore size distribution, tuneable pore size, adjustable hydrophobicity and very good thermal stability. Zn/MCM-41/O2 microsystem showed promise for near future use in RFID applications and, cosmetic and drug delivery patches.